e-book Multimedia Animation Implementation on Concept Mastery and Problem-Solving Skills of Crystal Structure Subjects in Engineering Materials Course - Amay Suherman; Mumu Komaro; A. Ana (Indonesian Journal of Science and Technology, 2023)
This research is motivated by students’ difficulties in understanding abstract, complex, and dynamic concepts in the learning process of the Engineering Materials course. The course is very important because it is indispensable for advanced study program expertise courses. The purpose of the research is to analyze the impact of using the e-book Multimedia Animation (e-MMA) in the learning process of engineering materials courses on improving students’ learning outcomes in the crystal structure subject. The research used an experimental method with a randomized control group pretest-posttest design. Two groups were assessed from two classes in Engineering Department randomly selected as the research sample. The subject that becomes the focus of this study is Crystal Structure to understand Concept Mastery and Problem-solving aspects. Thus, there will be two competency data from the research results. The application of e-MMA in the learning process of engineering materials can improve student learning outcomes with an increase in the high category N-gain. The E-MMA is very effective in solving the problems of students in understanding crystal structure subject in engineering materials courses because of their ability to provide images and animations of abstract objects. Students can easily understand the concepts and formulas that exist in the crystal structure subject of engineering materials course